How can meta-research be used to evaluate and improve the quality of research in the field of traditional, complementary, and integrative medicine? - Jeremy Y. Ng; Myeong Soo Lee; Jian-ping Liu; Amie Steel; L. Susan Wieland; Claudia M. Witt; David Moher; Holger Cramer (Integrative Medicine Research)
The field of traditional, complementary, and integrative medicine (TCIM) has garnered increasing attention due to its holistic approach to health and well-being. While the quantity of published research about TCIM has increased exponentially, critics have argued that the field faces challenges related to methodological rigour, reproducibility, and overall quality. This article proposes meta-research as one approach to evaluating and improving the quality of TCIM research. Meta-research, also known as research about research, can be defined as “the study of research itself: its methods, reporting, reproducibility, evaluation, and incentives”. By systematically evaluating methodological rigour, identifying biases, and promoting transparency, meta-research can enhance the reliability and credibility of TCIM research. Specific topics of interest that are discussed in this article include the following: 1) study design and research methodology, 2) reporting of research, 3) research ethics, integrity, and misconduct, 4) replicability and reproducibility, 5) peer review and journal editorial practices, 6) research funding: grants and awards, and 7) hiring, promotion, and tenure. For each topic, we provide case examples to illustrate meta-research applications in TCIM. We argue that meta-research initiatives can contribute to maintaining public trust, safeguarding research integrity, and advancing evidence based TCIM practice, while challenges include navigating methodological complexities, biases, and disparities in funding and academic recognition. Future directions involve tailored research methodologies, interdisciplinary collaboration, policy implications, and capacity building in meta-research.